2006
DOI: 10.1096/fj.05-5682fje
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization and engraftment of a human skin substitute using circulating progenitor cell‐derived endothelial cells

Abstract: We seeded tissue engineered human skin substitutes with endothelial cells (EC) differentiated in vitro from progenitors from umbilical cord blood (CB-EC) or adult peripheral blood (AB-EC), comparing the results to previous work using cultured human umbilical vein EC (HUVEC) with or without Bcl-2 transduction. Vascularized skin substitutes were prepared by seeding Bcl-2-transduced or nontransduced HUVEC, CB-EC, or AB-EC on the deep surface of decellularized human dermis following keratinocyte coverage of the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 40 publications
0
85
0
Order By: Relevance
“…Transplanted HUVEC transfected with an antiapoptotic gene, Bcl-2, 21,25 or HUVEC mixed with mesenchymal precursor cells 20 were shown to form stable blood vessels in SCID mice. Also, HUVEC-derived vessels in SCID mice were shown to increase overall tissue perfusion in an ischemic hindlimb model 20 and to effectively vascularize tissues, including skin substitutes 26 and three-dimensional skeletal muscle constructs. 27 This work has been extended recently to the problem of prevascularizing a cardiac patch with HUVEC in a nude rat with cyclosporine, 28 or SpragueDawley rats with immune suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplanted HUVEC transfected with an antiapoptotic gene, Bcl-2, 21,25 or HUVEC mixed with mesenchymal precursor cells 20 were shown to form stable blood vessels in SCID mice. Also, HUVEC-derived vessels in SCID mice were shown to increase overall tissue perfusion in an ischemic hindlimb model 20 and to effectively vascularize tissues, including skin substitutes 26 and three-dimensional skeletal muscle constructs. 27 This work has been extended recently to the problem of prevascularizing a cardiac patch with HUVEC in a nude rat with cyclosporine, 28 or SpragueDawley rats with immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…and vessel formation was only realized after the HUVEC were transfected with antiapoptotic genes (Bcl-2) or cotransplanted with supporting cells (mesenchymal stem cells, embryonic fibroblasts, or perivascular cell precursors) as HUVEC alone did not achieve stable vascularization in vivo. 20,21,25,26 Here, transplanted EC survival was obtained without genetic modification of the EC or without cotransplantation of supporting cells. Presumably, in this model the transplanted EC drive the remodeling process that results in both host EC and supporting cell recruitment required to create a stable vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Schechner and colleagues [30,31] pioneered the use of marrow-derived circulating EPCs to promote vascularization prior to skin graft transplantation. After ex vivo culture of EPCs on the collagen-based skin graft, EPCs revascularized and promoted the survival of the skin grafts with minimal immune response [32]. More recently, putative EPCs have been redefined as ECFCs to underscore their stem cell properties, including their robust proliferative potential, their ability to form secondary and tertiary colonies, and their capacity, in vivo, to form blood vessels de novo [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the direct incorporation into vessels, BOEC indirectly stimulate host angiogenesis. 52 Unlike previously assumed, 53 we and others have shown that BOEC secrete several GFs that modulate angiogenesis and wound healing 9,52 (Table 1). Interestingly, early outgrowth EPC (or the factors they secrete) have a stimulatory effect on tube formation by BOEC, 53 which makes a combination therapy of both cell types attractive.…”
mentioning
confidence: 81%
“…Cord blood: Many studies highlight the excellent outgrowth of BOEC from CB (CB-BOEC) and suggest them, due to their high expansion and vasculogenic potential, to be ideal candidates for (S)TE purposes. 43,52,56,57 Au et al examined the in vivo vessel formation capacity of CB-BOEC in combination with pericyte-like cells and noted firmly increased survival, vessel formation and stability in comparison with ABderived BOEC (AB-BOEC). 56 CB-BOEC formed stable vessels in a dermal PGA-PLLA matrix when cotransplanted with SMC.…”
mentioning
confidence: 99%